Validation of molecular heterogeneity of Fluorescent Pseudomonas spp. and correlation with their potential biocontrol traits against fusarium wilt disease - Jayamohan, Nellickal Subramanyan; Patil, Savita Veeranagouda; Kumudini, Belur Satyan (Agriculture and Natural Resources, 2018)
Fluorescent Pseudomonas (FPs) are major rhizospheric bacteria with a variety of plant growth promotion attributes having potential field applications. The genomic and outer membrane protein (OMP) diversity were valued of 11 shortlisted FPs exhibiting potential biocontrol activity. The taxonomic diversity of isolates was studied using genomic fingerprinting assays-drandom amplification of polymorphic DNA (RAPD), enterobacterial repetitive intergenic consensus (ERIC), BOX, repetitive extragenic palindromic (REP) and (GTG5), and OMP analysis with sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Genomic diversity parameters were calculated: total allelic number, polymorphic information content, expected heterozygosity, dominance, and the Shannon and Simpson indices. All isolates were used to prime tomato seeds and plants were challenge-inoculated with Fusarium oxysporum and the disease incidence was assessed under greenhouse condition. Cluster analyses of RAPD and combined Rep analyses classified isolates into two major clusters. SDS-PAGE analysis of OMP resulted in bands in the range 29-66 kDa. Furthermore, the isolates treated with tomato seeds followed by challenge inoculation with F. oxysporum under greenhouse conditions showed that the three FPs, M80 (SUB1688209 Seq1 KX570929), M96 (SUB1688209 Seq1 KX570930) and T109 (SUB1688209 Seq1 KX570931) were able to induce systemic resistance. The study examined the possible correlation between strain-specific molecular diversity of FPs and provided an account of their potential biological control activity against F. oxysporum.